Cypermethrin, Chlorpyrifos and Endosulfan Toxicity to Two Non-Target Freshwater Organisms - Mugni, Hernan Diego (2012)
Pesticide consumption has increased considerably over the last decades in the Argentine Pampa. The persistence of toxicity of three commonly used insecticides to two regionally abundant organisms was assayed at environmentally realistic conditions. To simulate a runoff event, insecticides were added to aquariums containing water and sediment collected from a representative stream. The toxicity of insecticides formulations containing cypermethrin, chlorpyrifos and endosulfan to the amphipod Hyallela curvispina and the fish Cnesterodon decemmaculatus was assessed with laboratory bioassays conducted on water taken from the aquariums immediately after pesticide addition and every 2 to 3 days thereafter until toxicity ceased. Endosulfan did not cause mortality to H. curvispina at a nominal concentration of 1 µg/L. Cypermethrin and chlorpyrifos caused 100% mortality immediately after application at this concentration. Toxicity ceased 4 days after addition of chlorpyrifos, and 9 days after addition of cypermethrin, resulting in a 50% lethal time of 3 and 4 days, respectively. C. decemmaculatus demonstrated no mortality at 1 µg/L nominal concentration of the formulated insecticides assayed. At a dose of 5µ/L, no mortality was exhibited for cypermethrin and chlorpyrifos, while endosulfan produced 100% mortality immediately after application, but no significant toxicity 2 days after application. Present results suggest short persistence of toxicity of the commonly used insecticide formulations in Pampasic surface waters.